Modern methods for treating fractures in the distal epimetaphysis of the radial bone (a review of literature) - Zazirniy, Igor; Vasylenko, Anton (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The authors present PubMed materials from 2000 to 2011 on the choice of tactics of treatment for fractures in the distal epimetaphysis of the radial bone, the mechanism of this injury, its classification and diagnosis. Despite an apparent completeness in the examination of this problem, the choice of the tactics for its treatment is disputable. For this reason the authors examined the problem in order to reveal modern approaches in the surgical treatment of fractures in the distal epimetaphysis of the radial bone depending upon their stability.